Efektifitas Musik Nature sounds dan Dzikir Terhadap Penurunan Tingkat Depresi Pasien Kanker Payudara - Wahyuningsih, Indah Sri; Endah Janitra, Fitria; Melastuti, Erna (Universitas Muhammadiyah Magelang, 2020)
Depression is one of the psychological responses experienced by breast cancer patients. One of the actions to reduce the psychological impact of breast cancer patients is with music therapy. Music effects can calm the soul, provide comfort, calm, so that arises a sense of enthusiasm and positive thoughts. The music used in this study is nature sounds. This music is very close to the environment and each individual recognizes the sounds of nature so that it is more easily and efficiently applied. Natural sound music with a combination of dzikir can be used as an alternative therapy to improve the mental status of breast cancer patients who experience depression. This study aims to determine the effect of combination therapy of nature sound and dhikr on the level of depression in breast cancer patients. The method used in this study is a quasi-experimental approach with a pre-equivalent non-equivalent without control group approach, to see differences in the average level of depression before and after giving a combination of music therapy and dhikr. Giving music therapy is given with a rhythm of 60-80 bpm, stable, low frequency and relaxing melody has been done 2 times a week. The data was processed with SPSS statistical software version 20.0 with normality test and paired t test. The results showed that the majority of patients aged 36-45 years (46.7%) and undergoing 3rd cycle chemotherapy (33.3%). Natural sound music therapy and dzikir significant to reduce depression scores with p value = 0.001. In conclusion, this study proves that nature sounds music therapy effectively to reduce depression scores in breast cancer patients